2021
DOI: 10.1016/j.ejrad.2021.109686
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a candidate instrument to assess image quality in digital mammography using ROC analysis

Abstract: To validate a candidate instrument, to be used by different professionals to assess image quality in digital mammography (DM), against detection performance results. Methods: A receiver operating characteristics (ROC) study was conducted to assess the detection performance in DM images with four different image quality levels due to different quality issues. Fourteen expert breast radiologists from five countries assessed a set of 80 DM cases, containing 60 lesions (40 cancers, 20 benign findings) and 20 norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Sensitivity was 74% when specificity was similar to mammography (Criteria #1) and specificity was 76% when a highly sensitive diagnostic was achieved (Criteria #2). As mentioned, AUC of 0.85 is considered excellent (>0.8) (41), and not only well exceeds criteria (0.73), but exceeds all AUC values identified in studies on mammography (0.54-0.84) (12,31,40,(42)(43)(44)(45)(46).…”
Section: Algorithm Robustness and Configuration Selectionmentioning
confidence: 84%
See 1 more Smart Citation
“…Sensitivity was 74% when specificity was similar to mammography (Criteria #1) and specificity was 76% when a highly sensitive diagnostic was achieved (Criteria #2). As mentioned, AUC of 0.85 is considered excellent (>0.8) (41), and not only well exceeds criteria (0.73), but exceeds all AUC values identified in studies on mammography (0.54-0.84) (12,31,40,(42)(43)(44)(45)(46).…”
Section: Algorithm Robustness and Configuration Selectionmentioning
confidence: 84%
“…AUC greater than 0.7, 0.8 and 0.9 are considered acceptable, excellent and outstanding, respectively (41). The average ROC curve AUC value for mammography across eight studies was 0.73 (0.54-0.84 range), which will also be used to compare diagnostic success of the method presented in this paper (12,31,40,(42)(43)(44)(45)(46). Two overall accuracy criteria are suggested to show diagnostic potential for the algorithm presented:…”
Section: Diagnostic Criteriamentioning
confidence: 99%
“…Visual evaluation can be quite subjective and influenced by image aesthetics or personal preferences. Poor agreement levels have been demonstrated between expert readers on evaluation of the depiction of various features of the normal tissue [ 32 ]. Therefore, differences in the evaluations between the software and visual assessments do not necessarily indicate a problem with the software tool, but rather may indicate a difference in the techniques utilized by humans and software to verify the same positioning criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Responses to each question were restricted to a 7-point Likert scale In this pilot study only one experienced Medical Physics Expert was used as the reader. Interestingly Boita et al (2021) found that both physicist and radiologist instrument responses correlated well with radiologist detection performance [14].…”
Section: Methodsmentioning
confidence: 99%